Optimal production-inventory model for forest products industry supply chain under demand and supply uncertainty: Case study of a pulp mill in Ontario - Shashi Shahi; Reino Pulkki; Mathew Leitch; Christopher Gaston (Cogent Business & Management, 2017)
The production planning models used in the forest products industry do not recognize the demand and supply uncertainty, and as such do not work in unison with the inventory management models. An integrated production planning and inventory management model of a forest products industry is developed in this paper. The objective is to maximize the net annual profit of the forest industry under demand and supply uncertainty. The model is formulated as a simulation-based optimization model. A case study of a pulp mill in Northwestern Ontario shows that supply and demand uncertainty causes a net annual loss of 59.9 million to the pulp mill, whereas the introduction of a merchandizing yard in the supply chain not only absorbs shocks caused due to uncertainty, but also increases the net annual profit of the pulp mill to 26.7 million. However, the merchandizing yard is viable only if the sales price of pulp is above a threshold level. The integrated supply chain model can be applied to any forest products industry as it considers the entire supply chain structure and manages all business decisions both upstream and downstream in the supply chain.
Keywords: 650